Tetracycline Reduces Kidney Damage Induced by Loxosceles Spider Venom - Cinthya Kimori Okamoto; Carmen W. van den Berg; Mizuno Masashi; Rute M. Gonçalves-de-Andrade; Denise V. Tambourgi (Toxins, 2017)
Envenomation by Loxosceles spider can result in two clinical manifestations: cutaneous and systemic loxoscelism, the latter of which includes renal failure. Although incidence of renal failure is low, it is the main cause of death, occurring mainly in children. The sphingomyelinase D (SMase D) is the main component in Loxosceles spider venom responsible for local and systemic manifestations. This study aimed to investigate the toxicity of L. intermedia venom and SMase D on kidney cells, using both In vitro and in vivo models, and the possible involvement of endogenous metalloproteinases (MMP). Results demonstrated that venom and SMase D are able to cause death of human kidney cells by apoptosis, concomitant with activation and secretion of extracellular matrix metalloproteases, MMP-2 and MMP-9. Furthermore, cell death and MMP synthesis and secretion can be prevented by tetracycline. In a mouse model of systemic loxoscelism, Loxosceles venom-induced kidney failure was observed, which was abrogated by administration of tetracycline. These results indicate that MMPs may play an important role in Loxosceles venom-induced kidney injury and that tetracycline administration may be useful in the treatment of human systemic loxoscelism.